A case of livedoid vasculopathy, a thrombotic occlusive vasculopathy. Issue 1 (8th February 2022) - Huot, Anais; Maniu, Christa‐Maria; Bogiatzi, Sofia; Hohl, Daniel; Alberio, Lorenzo; Stalder, Gregoire
Abstract: Livedoid vasculopathy (LV) is a rare thrombotic occlusive vasculopathy presenting with chronic relapsing‐remitting bilateral painful skin ulcerations predominating on the ankles and dorsal surface of the feet. LV can be idiopathic or secondary to endothelial dysfunction, rheological disorder, haemostatic or fibrinolytic pathology. We describe the case of a 49‐year‐old patient with LV and summarise the current knowledge on epidemiology, risk factors, and treatment of this rare condition. It is important to differentiate LV from vasculitic disorders, the management of the latter being based on immunosuppression, whereas the treatment of LV is based on anticoagulant or antiplatelet therapy. Abstract : A 49‐year‐old male patient has been present for 2 years for recurrent painful ulcerations on the ankles and plantar face of his feet. On physical examination, scars were seen on the medial and lateral sides of both malleoli with the presence of cutaneous telangiectasia and 'atrophie blanche' (left panel). Skin lesion biopsy (right panel) shows numerous sites of neovascularization and telangiectasias in the superficial and mid dermis with foci of occluded capillaries (arrows) and extravasated red blood cells. There is a mild perivascular infiltrate, predominantly histiocytic. Areas of epidermal necrosis (asterisk) and incipient formation of a subepidermal blister are seen.